PENINGKATAN EFISIENSI ENERGI KIPAS SIRKULASI UDARA DI PANEL LISTRIK MELALUI PENGATURAN KECEPATAN - Tadeus, Dista Yoel; Mangkusasmito, Fakhruddin (Gema Teknologi, 2020)
Internal temperature of electric panel practically depend on the amount of power dissipation generated by the panel components and the outside temperature. If this equilibrium is not maintained then the internal temperature can increase too high beyond the working temperature limit for components so as to shorten the life of panel components. Generally, there are two fans installed to circulate the air inside the panel that operates atÂ  fixed speed. In order to improve fan energy efficiency, it is necessary to add a control system that can adjust the fan speed based on actual panel internal temperature. Efforts to increase energy efficiency are realized using cheap hardware and easily available on the market, the ATMEGA 8535 microcontroller and LM 35 temperature sensor. The fan speed is normalized in percent units and expressed virtually using the Pulse Width Modulation (PWM) signal value calculated by the proportional control algorithm inside the controller. The experimental results show that the PWM value can vary with actual panel internal temperature. Using the time constant temperature asumption k1 = 0.2, k2 = 0.4, k3 = 0.2, k4 = 0.2 and experimental data, it was shown by calculations that there was an increase in energy efficiency by 40.8%.